KESANTUNAN BERBAHASA DALAM ANIMASI ANAK NUSSA - Risti Meylinda; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2022)
AbstractThis research describes Language Politeness in Nussa Children's Animation. Politeness in language is speaking subtly whose contents have a clear purpose, soothe the heart, and make other people happy. The purpose of this study is to describe the application and forms of language politeness deviations, as well as the implementation of language politeness in learning Indonesian at school. This research uses descriptive method in the form of qualitative by using documentary study techniques. The source of data in this study is the animation of Anak Nussa in the form of speech or dialogue between characters. The data collection tool is the researcher as the key instrument assisted by notes in the form of inter-character speech containing the principle of politeness according to Leech in the Animation of Anak Nussa. The results of this study there are 51 utterances. The maxim of wisdom is 5 utterances, the maxim of generosity is 9 utterances, the maxim of appreciation is 9 utterances, the maxim of simplicity is 2 utterances, the maxim of agreement is 9 utterances, the maxim of sympathy is 6 utterances, the form of deviation of the maxim of wisdom is 4 utterances, the form of deviation of the maxim of simplicity is 4 utterances, and the form of deviation of the maxim of agreement amounted to 2 utterances.Keywords: Animation of the Nussa Children, Language, Politeness